2007
DOI: 10.1038/sj.onc.1210874
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin structure and DNA double-strand break responses in cancer progression and therapy

Abstract: Defects in the detection and repair of DNA double-strand breaks (DSBs) have been causatively linked to tumourigenesis. Moreover, inhibition of DNA damage responses (DDR) can increase the efficacy of cancer therapies that rely on generation of damaged DNA. DDR must occur within the context of chromatin, and there have been significant advances in recent years in understanding how the modulation and manipulation of chromatin contribute to this activity. One particular covalent modification of a histone variant-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…In this study, we showed that siRNA-mediated ablation of TIP60, a target of anacardic acid (Sun et al, 2006), suppressed NHEJ. The results also indicated that NHEJ is accomplished through chromatin modification by HATs (Valerie and Povirk, 2003;Downs, 2007), and that this assay system can be used to examine the molecular mechanisms involved in NHEJ in vivo, including that of HATs and other chromatin remodeling proteins. ChIP analysis showed that DSB-induced acetylation of lysines 5, 8, 12 and 16 within histone H4 occurs in both yeast and mammalian cells (Downs et al, 2004;Tamburini and Tyler, 2005;Murr et al, 2006).…”
Section: Discussionmentioning
confidence: 83%
“…In this study, we showed that siRNA-mediated ablation of TIP60, a target of anacardic acid (Sun et al, 2006), suppressed NHEJ. The results also indicated that NHEJ is accomplished through chromatin modification by HATs (Valerie and Povirk, 2003;Downs, 2007), and that this assay system can be used to examine the molecular mechanisms involved in NHEJ in vivo, including that of HATs and other chromatin remodeling proteins. ChIP analysis showed that DSB-induced acetylation of lysines 5, 8, 12 and 16 within histone H4 occurs in both yeast and mammalian cells (Downs et al, 2004;Tamburini and Tyler, 2005;Murr et al, 2006).…”
Section: Discussionmentioning
confidence: 83%
“…The γH2AX foci are the markers of DNA damage breaks, incomplete DNA replication and local abnormal chromatin structure. 11,12 Although HDACI are not DNA-damaging agents, they can influence chromatin structure, DNA repair and activity of DDR signal transduction pathways. [12][13][14] The data demonstrate that untreated Waf1 +/+ and Waf1 -/-transformed cells show negligible γH2AX foci staining, which becomes evident in the course of NaB treatment (Sup.…”
Section: Waf1mentioning
confidence: 99%
“…[12][13][14][15][16][17] These include drugs of the R-CHOP regimen (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) [18][19][20][21][22][23] as well as drugs of second-line regimens containing platinum compounds. 24,25 Tumor cells respond to DNA damage induced by chemotherapy by activating 5 major DNA repair pathways: (1) mismatch repair (MMR), [12][13][14] (2) base excision repair, [12][13][14] (3) nucleotide excision repair, [12][13][14] (4) double strand break repair, 15 and (5) direct reversal. 16 MMR, of which MLH1 is a major component, recognizes and removes mismatched or unmatched DNA base pairs or insertiondeletion loops.…”
Section: Introductionmentioning
confidence: 99%